Long-term autogenous healing and re-healing performance in concrete: Evaluation using air-coupled surface-wave method. (8th November 2021) - Ahn, Eunjong; Kim, Hyunjun; Park, Byoungsun; Shin, Myoungsu
Highlights: Long-term autogenous healing and repetitive healing in concrete were investigated. The healing prediction model is reasonably accurate for the tracking healing rates. Satisfactory re-healing is achieved for the narrowest re-opened crack width. Air-coupled surface-wave tests are effective to evaluate crack-healing performance. Abstract: This study aimed at investigating two original topics on self-healing concrete, 1) the prediction of long-term healing progress and 2) the evaluation of re-healing performance for a previously healed but reopened crack, using the air-coupled surface-wave method. Small-scale plate concrete specimens were fabricated with a self-healing binder incorporating ground granulated blast furnace slag, Na2 SO4, anhydrite, and graded clinkers. A single flexural crack of 0.25–0.30 mm width was generated near the mid-span of each specimen. Then, the specimens were kept immersed in water, and the healing progress of the cracks was monitored for approximately one year. As a result, the residual surface crack area was reduced to 15.1% of the fully-cracked condition, and the surface wave transmission ratio recovered up to 82.9% of the uncracked condition. A prediction model for the ultimate healing rate and initial healing rate was proposed based on surface-wave results. After the first self-healing process, the specimens were loaded again, and a similar crack was produced at the previously healed zone in each specimen. Then, the re-healing performance was evaluated for about two months. From the second self-healing process, one specimen with a narrow reopened crack showed a satisfactory recovery in surface wave transmission, comparable to that in the first healing.